Dynamic and steady state performance model of fire tube boilers with different turn boxes. (25th February 2019) - Beyne, Wim; Lecompte, Steven; Ameel, Bernd; Daenens, Dieter; Van Belleghem, Marnix; De Paepe, Michel
Highlights: A fire tube boiler heat transfer model is developed and validated. The effect of the turn box on overall performance is checked. Part load capability is investigated for several designs. Model variants are compared for accuracy and grid convergence. Abstract: The market for fire tube boilers is increasingly demanding custom designs from the manufacturers. For these new designs, a comprehensive thermal model is needed. In this article, both a steady state and dynamic thermal model is developed based on the plug flow furnace model with general experimental correlations. The steady state model allows optimizing (i.e. safely downsizing) boiler designs. This model has been verified with measurement reports. The dynamic model is used to estimate the peak load capability of a boiler. In the presented case, the fire tube boiler can produce up to 2.5 times the nominal steam flow rate for a period of 10 min. Special attention has been paid to the turn boxes and their specific placement, which other models in literature neglect. The efficiency penalty of a non-submerged turn box can reach up to 12% but can be reduced significantly by insulation. Turn boxes also affect peak load capability. If the total length of the boiler is constant, submerging the turn box has a positive effect on the peak load capability. This effect is mostly attributed to the increased water volume. Finally, the article includes a comparison between the plug flow furnace model the ε-NTU method and the ε-NTU method with inclusion of radiation to model the tube passes. The ε-NTU method with inclusion of radiation allows to significantly reduce the necessary number of control volumes without reduction in the model accuracy.